Theaflavin-3,3′-Digallate from Black Tea Inhibits Neointima Formation Through Suppression of the PDGFRβ Pathway in Vascular Smooth Muscle Cells - Wu, Yichen; Chen, Min; Chen, Zilong; Shu, Jiangcheng; Zhang, Luoying; Hu, Jiong; Yu, Hongjun; Huang, Kai; Liang, Minglu (Frontiers in Pharmacology, 2022)
The abnormal neointima formation caused by the phenotypic switching of vascular smooth cells (VSMCs) into a synthetic state plays a key role in the pathogenesis of various vascular diseases, including atherosclerosis and postangioplasty restenosis. Theaflavin-3,3′-digallate (TF3) in black tea has been reported to exert antiinflammatory and anticancer effects, but its role in neointima formation remains unclear. Here, we delineated a remarkable effect of TF3 in suppressing neointima formation of VSMCs in vivo as well as the ability of primary rat aortic smooth cells (RASMCs) to proliferate and migrate in vitro. Further study confirmed that the effects of TF3 on PDGF-BB–induced RASMCs were due to reduced phosphorylation of PDGFRβ, which led to the repression of downstream pathways. We concluded that TF3 may act as a repressor in the progression of neointima formation and serve as a potential therapeutic candidate for excessive phenotypic switching of VSMCs.